Polyphenols and Phenolic Glucosides in Antibacterial Twig Extracts of Naturally Occurring Salix myrsinifolia (Salisb.), S. phylicifolia (L.) and S. starkeana (Willd.) and the Cultivated Hybrid S. x pendulina (Wender.) - Enass Salih; Eunice Ego Mgbeahuruike; Stella Prévost-Monteiro; Nina Sipari; Henry Väre; Brigita Novak; Riitta Julkunen-Tiitto; Pia Fyhrqvist (MDPI AG, 2024)
(1) Background: Salix species occurring in Finland have not been well studied for their antimicrobial potential, despite their frequent use for lung and stomach problems in traditional medicine. Thus, twig extracts of three species of Salix that are found naturally in Finland and one cultivated species were screened for their antimicrobial properties against human pathogenic bacteria. S. starkeana and S. x pendulina were screened for antibacterial effects for the first time. (2) Methods: An agar diffusion and a microplate method were used for the screenings. Time-kill effects were measured using a plate-count and a microplate method. A DPPH-method using a qualitative TLC-analysis was used to detect antioxidant compounds in antimicrobial extracts. Metabolites from a S. myrsinifolia extract showing good antibacterial effects were identified using UPLC/QTOF-MS. (3) Results: A methanol extract of S. starkeana was particularly active against B. cereus (MIC 625 µg/mL), and a methanol extract of S. myrsinifolia showed good activity against S. aureus and B. cereus (MIC 1250 µg/mL) and showed bactericidal effects during a 24 h incubation of B. cereus. Moreover, a decoction of S. myrsinifolia resulted in good growth inhibition against P. aeruginosa. Our UPLC/QTOF-MS results indicated that proanthocyanidins (PAs), and especially the dimer procyanidin B1 (m/z 577) and other procyanidin derivatives, including highly polymerized proanthocyanidins, were abundant in S. myrsinifolia methanol extracts. Procyanidin B1 and its monomer catechin, as well as taxifolin and p-hydroxycinnamic acid, all present in S. myrsinifolia twigs, effectively inhibited B. cereus (MIC 250 µg/mL). (4) Conclusions: This study indicates that Finnish Salix species contain an abundance of antibacterial condensed tannins, phenolic acids and other polyphenols that deserve further research for the antibacterial mechanisms of action.